"Part of the Solution:" Food Corporation Strategies for Regulatory Capture and Legitimacy - Jennifer Lacy-Nichols; Owain Williams (Kerman University of Medical Sciences, 2021)
Background  For decades, the food industry has sought to deflect criticisms of its products and block public health legislation through a range of offensive and defensive strategies. More recently, food corporations have moved on to present themselves as "part of the solution" to the health problems their products cause. This strategic approach is characterised by appeasement, co-option and partnership, and involves incremental concessions and attempts to partner with health actors. This paper details how corporate practices have evolved and changed over the past two decades and gives some definition to what this new political economy signifies for the wider behaviours of corporations producing and selling harmful commodities. Methods  This paper draws on public health and political science literature to classify the food industry's "part of the solution" strategy into three broad components: regulatory responses and capture; relationship building; and market strategies. We detail the key characteristics and consequences of each component.Results  The three components of the food industry's "part of the solution" strategy all involve elements of appeasement and co- option. They also improve the political environment and resources of the food industry. Regulatory responses offer incremental concessions that seek to maintain corporate influence over governance processes and minimise the threat of regulations; relationship building fosters access to health and government stakeholders, and opportunities to acquire and maintain channels of direct influence; and market strategies to make products and portfolios healthier bolster the market share and revenue of food corporations while improving their public image. Conclusion  Rather being a signal of lost position and power, the food industry's repositioning as "part of the solution" has created a highly profitable political economy of 'healthy' food production, alongside continued production of unhealthy commodities, a strategy in which it is also less burdensome and conflictual for corporations to exercise political power and influence.